2020
DOI: 10.1002/brb3.1912
|View full text |Cite
|
Sign up to set email alerts
|

Fat compartments in patients with depression: A meta‐analysis

Abstract: Introduction Depressive disorders are a common illness worldwide. Major depression is known as a significant predictor of the metabolic syndrome. However, the effects of depression on adipose tissue compartments are controversial. This meta‐analysis aimed to evaluate the state of research on the relationship between patients with depression and adipose tissue compartments as compared to nondepressed individuals. Methods The PubMed database was searched for human studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The findings of higher body fat in both patient groups (vs. healthy controls) widen the results of our former research, which demonstrated that higher body fat mass and lower body muscle mass correlated significantly with stronger depression severity ( 34 ). It also agrees with former studies showing elevated body fat to associate with depressive symptoms ( 26 , 35 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of higher body fat in both patient groups (vs. healthy controls) widen the results of our former research, which demonstrated that higher body fat mass and lower body muscle mass correlated significantly with stronger depression severity ( 34 ). It also agrees with former studies showing elevated body fat to associate with depressive symptoms ( 26 , 35 ).…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the antidepressant effect of adjunctive treatment with statins is well-known ( 24 ). Enlarged visceral adipose tissue is associated with dyslipidemia [characterized by hypertriglyceridemia, high LDL, and reduced high-density lipoprotein (HDL) cholesterol levels] ( 25 ) and common depression symptoms ( 26 ). Sedentary behavior and elevated triglycerides are associated with higher depression risk ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…MDD is linked to several comorbidities potentially associated with adverse cardiovascular outcome. This includes the dysregulation of the hypothalamus-pituitary-adrenal axis [38], ectopic fat compartments [39] and life style changes (particularly low physical activity, increased BMI and increased smoking behaviour) [40,41]. In particular, persisting MDD decreases adherence, contributing to an increased mortality in patients with acute coronary syndrome, thereby pointing to the importance of identifying MDD in the context of cardiovascular disorders [42].…”
Section: Prognostic Value Of Reduced Heart Rate Variability and Mddmentioning
confidence: 99%
“…Overall, two recent meta-analyses concluded that MDD as well as self-reported depressive symptoms were associated with enlarged VAT compartments. This association appears independent of sex, age, and method of VAT content assessment (i.e., MRI or CT) as well as method of depression assessment ( 97 , 98 ). Additionally, the association of VAT with depression remained significant when only studies controlling for BMI were taken into account ( 98 ).…”
Section: Intrathoracic Cardiac Adipose Tissue and Depressionmentioning
confidence: 82%